African Indigenous Vegetables Production and Consumption Behavior of Farmers in Zambia: An Econometric Analysis - Arumugam, Surendran; Govindasamy, Ramu; E. Simon, James; Wyk, Emil Van; Chali, Kenneth; Mbewe, Mwangala; Siziya, Inonge; Weller, Steve; K. Morin, Xenia (Technium Social Sciences Journal, 2020)
African indigenous vegetables (AIVs) have recently received wide attention for their contribution toward food and nutrition security. Promoting the production and consumption of AIVs is likely to mitigate food insecurity and alleviate malnutrition in the African region. To document and analyze existing patterns of AIV production in Zambia, farmers were surveyed in person using a structured questionnaire. A total of 300 farmers were selected from Lusaka (50), Katete (50), Chipata (75), Lundazi (75), and Petauke (75). Analysis of the survey results using logit model identified that those who farm less than 10 acres of farming land, were concerned about nutrition quality of AIVs, reported that price of farm produce is fixed by buyers, were registered as a member of any community group or association, received training related to nutrition and health, saved money for unexpected expenses, and were single are more likely than other farmers to produce AIVs for home consumption. Whereas, those who visited the nearest market two times or more, traded agricultural produce through intermediaries, owned a TV, earned an income above 30,000 kwacha and has a University degree are less likely to produce AIVs for home consumption. These results indicate that interventions aimed at increasing AIV production for home consumption should target specific groups of farmers rather than all farmers. This survey also captures the most common AIVs that are grown in these regions in Zambia: Sweet potato leaves, amaranth and orange sweet potato.